Nieprzezroczystość ekfrazy: reprezentowanie, zapośredniczanie i przekład w opisach artefaktów - Słodczyk, Rozalia (Przestrzenie Teorii, 2019)
The article concentrates on the non-transparency of ekphrasis, including the relevance - in the case of a full, in-depth analysis of particular ekphrasis - not only of the description but also of the artefact itself. The text reflects upon subjects rarely dealt with in ekphrasis research, such as on the meaning and relations of the concepts ‘presentation’ and ‘representation’. There is a focus on the question of multi-layered mediation, which is related to this discourse figure: through language, through the viewer’s perspective who writes about the work, through the reader themself, and also, or perhaps first and foremost, through the work itself. This all results in ekphrasis being treated as a representation of representation. This also gives rise to thoughts on the problem of translating the visual system to verbal and the issues related to this.